Association Between Dystonia-Related Genetic Loci and Parkinson's Disease in Eastern China - Yang, Wen-Yi; Jiang, Si-Si; Pu, Jia-Li; Jin, Chong-Yao; Gao, Ting; Zheng, Ran; Tian, Jun; Zhang, Bao-Rong (Frontiers in Neurology, 2022)
Background: Parkinson's disease (PD) and dystonia are closely related in terms of pathophysiology and clinical manifestations, but their common genetic characteristics remain unclear. Some genome-wide association studies (GWAS) and replication studies have revealed correlations between single nucleotide polymorphisms (SNPs) of the ARSG, BDNF, NALCN, OR4X2, KIAA1715, and OR4B1 genes and dystonia. This study was conducted to assess the association between these genetic loci and PD in a population from Eastern China. Methods We genotyped the SNPs (rs11655081 of ARSG; rs6265 of BDNF; rs61973742, rs1338051, rs9518384, and rs9518385 of NALCN; rs67863238 of OR4X2; rs10930717 of KIAA1715; and rs35875350 of OR4B1) in a cohort of 474 patients with PD and 439 healthy controls from East China. To determine the genotypes of these SNPs, we used an Agena MassARRAY Typer 4.0. Odds ratios (ORs) and 95% confidence intervals (CIs) were computed to evaluate the correlations between these SNPs and the risk of PD. Results There were significant differences in the genotype distribution (OR=0.649, 95%CI=0.478-0.880) and minor allele frequency (MAF) (OR=0.703, 95%CI=0.533-0.929) of SNP rs61973742 (NALCN) between patients with PD and healthy controls. A significant difference was also detected in the genotype distribution of rs11655081 (ARSG) (OR=1.486, 95%CI=1.080-2.045). Conclusion SNPs rs11655081 (ARSG) and rs61973742 (NALCN) may be associated with PD. The C allele of rs11655081 may increase the risk of PD, whereas the G allele of rs61973742 may be a protective factor.